2000
DOI: 10.1063/1.1323504
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent quantum wave packet studies of the F+HCl and F+DCl reactions

Abstract: Full three-dimensional time-dependent quantum wave-pack calculations have been carried out for the F+HCl and F+DCl reactions on a many-body expansion of the ground 2A′HClF potential energy surface. The calculated energy-dependence of reaction probability exhibits oscillating structure in the F+HCl reaction but not in the F+DCl system. The effects of initial state excitation on the total reaction probabilities as a function of collision energy are investigated for reactions from various initial vibrational and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 40 publications
1
30
1
Order By: Relevance
“…Sayos et al recently carried out an ab initio calculation at 311G(3d2f,3p2d) level using PUMP2/ PUMP4 method at 3400 geometries [12]. Based on the Sayos's PES, classical trajectory simulations [13] and quantum time-dependent wave packet dynamics calculations have been performed [14]. Enhancement of the reaction probability from reagent rotational excitation has been observed on Sayos's PES.…”
Section: Introduction Fmentioning
confidence: 95%
“…Sayos et al recently carried out an ab initio calculation at 311G(3d2f,3p2d) level using PUMP2/ PUMP4 method at 3400 geometries [12]. Based on the Sayos's PES, classical trajectory simulations [13] and quantum time-dependent wave packet dynamics calculations have been performed [14]. Enhancement of the reaction probability from reagent rotational excitation has been observed on Sayos's PES.…”
Section: Introduction Fmentioning
confidence: 95%
“…3,7,9 It has been demonstrated for this kind of systems that it is more efficient to use product Jacobi coordinates in wave packet calculations. 13 The present state-to-state reaction probabilities are calculated using a wave packet method, with the MADWAVE3 code recently developed by Zanchet et al 14 The MADWAVE3 code has been well documented in the literature 14,15 and only the details relevant to the present work will be given here.…”
Section: Methodsmentioning
confidence: 99%
“…The title reaction has been the subject of many theoretical [1][2][3][4][5][6][7][8][9] and experimental [10][11][12] studies. Experimentalists, have focused on the determination of thermal rate constants.…”
Section: Introductionmentioning
confidence: 99%
“…This value was then empirically reduced to 1.1 kcal/mol to obtain the experimental rate. QCT 12 as well as QM 13 calculations performed on this surface have been reported to analyze the reaction dynamics for both the title reaction and its deuterium isotope variant. Recently, a new benchmark ab initio PES(hereafter referred to as DHSN) for the 1 2 A state of FHCl has been constructed by Deskevich et al 14 Using this DHSN potential energy surface, the same group performed detailed quasiclassical trajectory(QCT) and quantum mechanical studies 15 of the title reaction, having found that the reagent rotation have a dramatic effect on the reaction probability.…”
Section: Introductionmentioning
confidence: 99%